Gerakan Sosial Baru Tolak “Formula-E” Dengan Studi Kasus Ruang Publik Jurgen Habermas - Putra, Michael Dwi; Erawan, I Ketut Putra; Noak, Piers Andreas (Jurnal Nawala Politika; 2020: Jurnal Ilmu Politik 2020, 2025)
This study examines how the New Social Movement "Refuse Formula-E" which is in the public sphere in its implementation, everyone has equal rights and authority in expressing opinions in public, in addition to the theory of the Public Space itself, the movement carried out should not be intervened by the public. any party so that this Movement does come from the community, on the other hand the community groups that carry out this action are also strengthened by community groups that have no affiliation or cooperation with any party or state institution, besides that several actions are also carried out on social media, current developments This makes the movement or action can be carried out online and is more efficient to carry out and reach more people, in this movement the public space does exist and is felt by the community, but many people still do not understand about expressing opinions even though there is a law that guarantee the right to give opinion.